Comfort in contemporary culture - Birke, Dorothee,Butter, Stella (transcript Verlag, 2020)
Long description: Comfort is a prominent and highly loaded concept, as popular discourses on cozy environments, safe spaces, but also the importance of »getting out of your comfort zone« attest. This volume is the first to investigate »comfort« as a cultural narrative and emotional touchstone in contemporary culture. Taken together, the contributions to the volume offer an overview of different approaches to and conceptualizations of comfort in linguistics, literary, media, and cultural studies and art history. They showcase how »comfort« serves as a valuable lens to analyze contemporary artworks and developments, e.g. live theatre broadcasting or political interventions in the US-American media sphere Biographical note: Dorothee Birke is a visiting professor of English studies at the University of Innsbruck. Her main research interests include political drama, digital book culture, and the history of the novel. She has held fellowships at the Freiburg Institute for Advanced Studies and the Aarhus Institute of Advanced Studies. Stella Butter is a professor of English and American literature at the University of Koblenz-Landau (Campus Landau). In her research, she is especially interested in representations of home in contemporary Anglophone literature, contingency and literature, and the cultural functions of the British novel in the process of modernization
Keywords: Aufsatzsammlung; Film; Culture; Media; Cultural History; Cultural Theory; Cultural Studies; literature; Literary Studies; Kultur; Bequemlichkeit; Diskurs